Tackling Corruption in Indonesia: Lessons Learned and Future Directions - Ilham, Muh (Journal of Public Representative and Society Provision, 2022)
The aims of the study to know tackling corruption in Indonesia. This paper uses a qualitative approach to assess the existing and proposed measures with regard to combating corruption in the context of studing Indonesia through the review of published academic and grey literature and series of interviews with a pool of selected informants consisted of officials, academics, and civil activist/Non-Government-Organization actors. The study confirms that corruption is systemic, and its occurrence is instituting, across the sectors, including civil society organizations, which often participate in corrupt practices. Describing the main findings of the research, the paper also points out that political will and leadership are the two factors that can affect the success of anti-corruption measures; at the same time, the paper also shows that there is an emerging contradiction between the words and actual actions in Indonesia and presented the KPK as an example of institution weaker due to the ideology gap. Lack of coordination of different organizations fighting corruption, also coupled with institutional fragmentation makes it even more difficult to fight the vice. Even though there are good laws in place, the enforcement and institutional measures are very weak and insufficient in many cases. It also highlights the social-economic impacts of corruption for democracy including its contribution to social- economic-economic imbalance and citizens’ disillusionment with government in the country.